ACTIVITE DE L’ALPHA AMYLASE SERIQUE ET SALIVAIRE DES SUJETS ADULTES CONSOMMATEURS HABITUELS DE DEUX BOISSONS ALCOOLISEES LOCALES DU BENIN - Gomina, Moutawakilou; Seni, Mustapha; Akpona, Simon Ayélèroun (European Scientific Journal, ESJ, 2013)
﻿Introduction: the effect of alcohol on the activity of α-amylase in serum and saliva raises many controversies. The objective of this study was to study the activity of α-amylase in serum and saliva of adults subjects habitual consumers of two local alcoholic beverages in Benin. Methods: we conducted a cross-sectional descriptive and analytical study from April 1 to August 31, 2012. Usual consumers of tchoukoutou and sodabi and those non-consumers of both sexes were selected in the city of Parakou in Benin Republic. For each subject, blood and saliva samples were collected. The activity of α-amylase was determined by the kinetic enzymatic method. The Kruskal-Wallis test was used to compare means and linear regression to establish statistical relationships. Results: a total of 150 subjects were recruited (32 women). The mean age was 34.7 ± 9.32 years. The mean values of the activity of α-amylase in serum and saliva of subjects habitual consumers of sodabi respectively 154.44 ± 52.47 IU/L and 131694.3 ± 114126.7 IU/L were higher than those of non-users respectively 125.38 ± 75.38 IU/L and 86121.16 ± 60852.9 IU/L. The mean values of the activity of α-amylase in serum and saliva of subjects habitual consumers of tchoukoutou respectively 146.65 ± 59.10 IU/L and 94690.3± 64578.77 IU/L were higher than those of non-users. The differences were significant at serum α-amylase activity (p <0.05). The mean values of the activity of α-amylase in serum and saliva of the subjects habitual consumers of sodabi were higher than those of tchoukoutou consumers with no significant difference. The correlations between the activity of α-amylase in serum and saliva and duration of use on one hand and the daily average amount of alcohol consumed on the other hand were very strong. Conclusion: consumption of tchoukoutou and sodabi increase the activity of α-amylase in serum and saliva. The abuse of these two beverages should be avoided by people.